A Chiral Nitrogen Ligand for Enantioselective, Iridium‐Catalyzed Silylation of Aromatic C−H Bonds. Issue 4 (15th December 2016) - Su, Bo; Zhou, Tai‐Gang; Li, Xian‐Wei; Shao, Xiao‐Ru; Xu, Pei‐Lin; Wu, Wen‐Lian; Hartwig, John F.; Shi, Zhang‐Jie
Abstract: Iridium catalysts containing dative nitrogen ligands are highly active for the borylation and silylation of C−H bonds, but chiral analogs of these catalysts for enantioselective silylation reactions have not been developed. We report a new chiral pyridinyloxazoline ligand for enantioselective, intramolecular silylation of symmetrical diarylmethoxy diethylsilanes. Regioselective and enantioselective silylation of unsymmetrical substrates was also achieved in the presence of this newly developed system. Preliminary mechanistic studies imply that C−H bond cleavage is irreversible, but not the rate‐determining step. Abstract : Iridium works now : A new chiral pyridinyloxazoline ligand was developed, which enables enantioselective, intramolecular silylation of symmetrical diarylmethoxy diethylsilanes. Regioselective and enantioselective silylation of unsymmetrical substrates was also achieved in the presence of this newly developed system.